Combinatorial Fluorescent Molecular Sensors: The Road to Differential Sensing at the Molecular Level - Rout, Bhimsen; Motiei, Leila; Margulies, David (Synlett, 2014)
Combinatorial fluorescent molecular sensors constitute a unique class of analytical systems that integrate the properties of small-molecule luminescent sensors and cross-reactive sensor arrays (the so-called chemical ‘noses/tongues’). On the one hand, these sensors can differentiate between a wide range of analyte combinations and concentrations, akin to pattern-generating arrays. On the other hand, they can operate in the microscopic world, which macroscopic analytical devices cannot access. This feature article summarizes the different approaches that can be used for obtaining multianalyte detection by fluorescent molecular sensors. In particular, it highlights an exciting prospect in the analytical sciences: differential sensing at the molecular level.
Keywords: fluorescent molecular sensors; chemosensors; molecular logic gates; cross-reactive sensor arrays; pattern-based detection